Answer:
x= -3 x = 1/2 x=-2
Step-by-step explanation:
f(x)=(x+3) (2x-1)(x+2)
Set equal to zero
0 =(x+3) (2x-1)(x+2)
Using the zero product property
x+3 =0 2x-1 =0 x+2 =0
x= -3 2x =1 x = -2
x= -3 x = 1/2 x=-2
Answer:
I am pretty sure there are 10 people in line.
Since Ashley is the seventh person in line, we can deduce that <u><em>there are 6 people in front of her</em></u>.
Since the amount of people in front of her is "twice as many people as there are behind her," we can divide the value of the people in front of her in half to get the value of people behind her.
6/2 is 3, so <em>there are </em><u><em>3 people behind Ashley</em></u><em>. </em>
Now, lets add the amount of people in front of Ashley to the amount of people behind her. 3 + 6 = 9, and since Ashley is also in the line, we should add 1 to the sum.
9 + 1 = 10, so <u><em>there are 10 people in the line</em></u>.
Answer:
8 miles
Step-by-step explanation:
We start by calculating the distance between the two points
To calculate this, we use the distance formula
Let the distance be D
We have the formula as;
D = √(x2-x1)^2 + (y2-y1)^2
D = √(-2+2)^2 + (-5-3)^2
D = √(64)
D = 8 units
Since 1 unit is 1 mile,
then 8 units will be 8 * 1 = 8 miles